Analysis of Cost deviation in civil works of selected hydropower projects of Province No. 1 and Gandaki Province - K.C., Aarshika (Everest Advances in Science and Technology, 2025)
Cost of construction project is one of the major concerns of the parties involved in the project. The percentage of difference between the initial cost and final cost is known as cost deviation. In the context of developing countries like Nepal, inadequate planning often leads to significant cost deviation in construction projects. A case study has been done observing four hydropower projects: Rudi Khola A, Hewa Khola HEP, Midim Khola HEP and Mistri Khola HEP. The objective was to analyze the current scenarios of cost deviation, identifying underlying causes and suggesting remedial measures to mitigate such deviations. Data were collected through the bill of quantities, final Interim Payment Certificates (IPCs), and questionnaire survey. The qualitative response from the questionnaire survey has been quantified with five point ranking Likert scale for analysis.The study revealed that the percentage deviation in cost lies between 18 % to 42 %. The main causes of cost deviation were identified separately .i.e. In Rudi Khola A HEP and Hewa Khola HEP, quantity overrun was the main cause. In Midim Khola HEP, change in design, quantity over run were identified as the major causes. In case of Mristi Khola HEP, seepage water management inside tunnel and price escalation were main causes of cost deviation.Based on the feedback of the parties involved, the remedial measures suggested are to review and improve bid documents such as technical specifications, drawings, bill of quantities by the consultant; contractor should have enough cash before beginning of any project, frequent preventive maintenance of equipment by hiring full time skilled mechanics; client should ensure quality design of the project and other measures as effective strategic planning, geological investigation should be done